PERAN AUDIT INTERNAL DALAM PENGUNGKAPAN KELEMAHAN MATERIAL SEBAGAI PENUNJANG TATA KELOLA PERUSAHAAN YANG BAIK - Samatha Adisty Ekasiwi; Endang Kiswara (Diponegoro Journal of Accounting, 2013)
This study aims to analyze the factors and the role of internal audit that affect the likelihood of disclosure of material weaknesses in the company in Indonesia. This research study is a replica of Lin et al. where the difference with previous studies is the study conducted in Indonesia and had conducted a survey using a questionnaire first. There are six variables that might impact on the disclosure of material weaknesses in the company. The three variables are indicators of the Attributes of Internal Audit Function (IAF), namely competence, objectivity, and investment. Three other variables are indicators of the Internal Audit Activity Function (IAF) is the grade of internal audits, follow-up and coordination.The results show the competence of internal auditors has no effect on the disclosure of material weaknesses, internal auditor objectivity positive influence on disclosure of material weaknesses, investments in internal auditor has no effect on the disclosure of material weaknesses, internal audit grade does not affect the disclosure of material weaknesses, follow-up on audit findings are not affect the disclosure of material weakness, and coordination between the internal auditor with the external auditor has no effect on the disclosure of material weaknesses.Implications of the results of research on good corporate governance, internal auditor competence is not in line with the principles of accountability, objectivity of internal auditors in line with the principles of transparency and independence, investment in internal auditors do not fit the principles of fairness and equity, internal audit grade do not meet the principles of accountability, follow-up audit findings has not been effective in accordance basic guidelines for transparency, coordination with external auditors can not satisfy the principle of independence.